Possibilities for management of conflicts among pre-school age children by applying methods of work with fairy-tales - Bražienė, Nijolė; Nemaniūnienė, Rita (Social Welfare: Interdisciplinary Approach, 2011)
The article introduces the qualitative research results of the pedagogical experiment which is aimed at the assessment of the impact of work with fairy-tales in development of pre-school age children’s ability to constructively solve arising conflicts among children. It was found out that fairy-tales could be the means for control of conflicts among pre-school age children when the content of fairy-tales and the process of their discussion were purposively oriented towards educated children’s ability to constructively manage conflict situations and strengthen social skills. When applying methods of the work with fairy-tales, it is possible to correct the attitude of children with problematic behaviour towards themselves and their relations with friends, to make impact on the internal condition of a child, i.e. to implement better self-assessment for those who are insufficiently aware of their role in group as well as to help those whose self-assessment is too high to see themselves from the point of view of others; positive changes of interpersonal social and communicative abilities (solution of problems, conflicts, initiative, tolerance, respect to each other etc.) were noticed in joint activities.
Keywords: conflict; pre-school age child; fairy-tale